2014
DOI: 10.1016/j.ssresearch.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the cigarette epidemic: An age-period-cohort study of education, gender and smoking using a pseudo-panel approach

Abstract: (online), with the title: Tracing the cigarette epidemic: An age-period-cohort study of education, gender and smoking using a pseudo-panel approach http://www.sciencedirect.com/science/article/pii/S0049089X14001033Tracing the cigarette epidemic: An age-period-cohort study of education, gender and smoking using a pseudopanel approach AbstractThis study examined if temporal variations in daily cigarette smoking and never-smoking among groups with different levels of education fit the pattern proposed by the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 59 publications
(75 reference statements)
2
28
0
Order By: Relevance
“…However, recently, several studies have attempted to perform APC analysis of smoking prevalence by combining crosssectional data for several years [20][21][22]. Veday [20] performed APC analysis of smoking prevalence in accordance with education level and gender and explained smoking prevalence in terms of social changes associated with each birth cohort and the theory of diffusion of innovations. Moreover, Veday [20] suggested that smoking prevalence declined with increasing education level via intercohort diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, several studies have attempted to perform APC analysis of smoking prevalence by combining crosssectional data for several years [20][21][22]. Veday [20] performed APC analysis of smoking prevalence in accordance with education level and gender and explained smoking prevalence in terms of social changes associated with each birth cohort and the theory of diffusion of innovations. Moreover, Veday [20] suggested that smoking prevalence declined with increasing education level via intercohort diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, this scenario assumes that smoking behaviours among 85 different age groups are stable. Given that smoking prevalence has decreased among each consecutive birth cohort over the last decades in most developed countries, 12,13 and that smoking has become more prevalent among older compared with younger birth cohorts in some countries, 19 it is possible that population ageing could compensate for decreasing smoking prevalence among younger age groups.…”
Section: Demographic Effects On Long Term Changes In Smokingmentioning
confidence: 99%
“…10,11 From a macrosocial point of view, long-term variations in smoking can be a result of people changing their behaviour because they grow older (age effects) and/or because new birth cohorts, with different smoking behaviours, enter the social system (cohort effects). 12,13 In addition, events at certain points in time may affect smoking among all groups, for example changes in taxation or new restrictions on where to smoke (period effects). 14,15 However, long-term variation in smoking prevalence may also result from changes in the demographic composition of a population (demographic effects).…”
mentioning
confidence: 99%
“…We address the identification problem by employing a solution from Deaton (1985), where temporal change is decomposed into birth-cohort dummies and a continuous age profile, while period effects are regarded as exogenous shocks that sum to zero in the long run. Based on Bell and Jones (2013) and Veday (2014), we assume that changes in smoking habits over time is the result of birth cohorts' differing attitudes toward smoking, rather than period effects, and allocate temporal trends to variations in age or cohort. (See also Veday, 2014.)…”
Section: Apc Models and The ''Identification Problem''mentioning
confidence: 99%